Strategi Pembelajaran Bahasa Indonesia Melalui Metode Mind Mapping dan Muatannya pada Profil Pelajar Pancasila - Nur Aini Indarwati; Edy Suryanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
One of the problems faced by Indonesian language teachers is the lack of student interest and motivation to learn Indonesian. Mind mapping is a visual technique that uses diagrams to represent ideas and relationships between concepts. This research aims to find out how the application of mind mapping learning strategies in Indonesian language learning and also its content on the Pancasila Student Profile. This research is a descriptive qualitative research. This research was conducted in class XI F4 SMAN 5 Surakarta with the object of research on the Indonesian language learning process of explanatory text material using mind mapping strategy. Data were collected through interviews, observations and documentation. The data were analyzed inductively to produce grounded theory. The results of this study indicate that mind mapping can improve student understanding because students are looking for their own problems and materials on the material provided. There were also some difficulties in the learning process such as the teacher's difficulty in coordinating the class, time constraints and student involvement. The content of the Pancasila Student Profile in this learning process is critical, responsible, mutual cooperation and critical thinking.